2018
DOI: 10.1200/jco.2017.77.6880
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genomic Characterization of Treatment-Emergent Small-Cell Neuroendocrine Prostate Cancer: A Multi-institutional Prospective Study

Abstract: The prevalence and features of treatment-emergent small-cell neuroendocrine prostate cancer (t-SCNC) are not well characterized in the era of modern androgen receptor (AR)-targeting therapy. We sought to characterize the clinical and genomic features of t-SCNC in a multi-institutional prospective study. MethodsPatients with progressive, metastatic castration-resistant prostate cancer (mCRPC) underwent metastatic tumor biopsy and were followed for survival. Metastatic biopsy specimens underwent independent, bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
701
4
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 580 publications
(770 citation statements)
references
References 35 publications
15
701
4
5
Order By: Relevance
“…These 216 genes represented a set of candidate NE‐specific genes suitable for model development. Only 19 genes were in common with the 69 SC/NE signature presented by Aggarwal et al …”
Section: Resultsmentioning
confidence: 99%
“…These 216 genes represented a set of candidate NE‐specific genes suitable for model development. Only 19 genes were in common with the 69 SC/NE signature presented by Aggarwal et al …”
Section: Resultsmentioning
confidence: 99%
“…However, further investigations are needed to confirm this association. Interestingly, recent large‐scale T‐SCNC‐related clinical studies conducted by Beltran et al and Aggarwal et al reported on two small‐cell NE carcinoma cohorts with median PSA levels of 0.38 and 64.8 with median survival times of approximately 10 and 36.7 months, respectively. The prognostic role of low PSA levels in patients with T‐SCNC thus needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Primary NEPC is a rare, highly malignant disease, accounting for only 1% of all newly diagnosed prostate cancers . It is not yet clear if primary NEPC and treatment‐induced small‐cell neuroendocrine prostate cancer (T‐SCNC) represent the same disease entity . However, a recent study suggested that primary small‐cell prostate cancer shared similar characteristics with T‐SCNC at the DNA and RNA levels, suggesting that the study of primary NEPC may provide clues relevant to T‐SCNC.…”
Section: Introductionmentioning
confidence: 99%
“…This may explain, at least in part, the more adverse clinical outcome of patients treated with docetaxel after A/E and the lack of association between TMPRSS2‐ERG and resistance to therapy. In a recently published study by Aggarwal et al ., the acquisition of NE phenotype was observed in 17% patients who progressed to abiraterone, and this was associated with adverse clinical outcome, but no data regarding to response to chemotherapy were reported . Other genetic markers such as RB1 and TP53 lost have been related to antiandrogen resistance therapy but no conclusive data have been reported in association with taxanes either .…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study by Aggarwal et al, the acquisition of NE phenotype was observed in 17% patients who progressed to abiraterone, and this was associated with adverse clinical outcome, but no data regarding to response to chemotherapy were reported. 22 Other genetic markers such as RB1 and TP53 lost have been related to antiandrogen resistance therapy but no conclusive data have been reported in association with taxanes either. 23 The predictive value of NE markers and other common genetic alterations in taxane-resistance have to be further defined.…”
Section: Discussionmentioning
confidence: 99%